The Representation of Unconditional Love In Feby Putri's Tanpa Pamrih Music Video: A Roland Barthes Semiotic Analysis - Rahma Aulia; R. Myrna Nur Sakinah (CV Edu Tech Jaya, 2026)
Music videos have evolved beyond promotional media into visual communication platforms that represent meanings through signs and symbols. One of the values frequently portrayed in visual narratives is unconditional love, expressed through sincerity, sacrifice, empathy, and compassion without expecting anything in return. This study aims to analyze the representation of unconditional love in Feby Putri's Tanpa Pamrih music video using Roland Barthes' semiotic approach. Employing a qualitative descriptive method, data were collected through observation, documentation, and literature review. The research data consisted of six scenes analyzed using Barthes' three levels of meaning: denotation, connotation, and myth. The findings indicate that Tanpa Pamrih represents unconditional love through visual symbols portraying sincerity, sacrifice, care, and acceptance. These meanings are constructed not only through the interactions between characters but also through the use of color, facial expressions, body gestures, visual composition, and cinematography, which collectively reinforce the cultural myth of love as a universal human value. The study concludes that unconditional love is represented through both interpersonal relationships and the relationship between humans and nature, reflecting care, gratitude, and responsibility.